2020
DOI: 10.3390/v12030293
|View full text |Cite
|
Sign up to set email alerts
|

Peste des Petits Ruminants at the Wildlife–Livestock Interface in the Northern Albertine Rift and Nile Basin, East Africa

Abstract: In the recent past, peste des petits ruminants (PPR) emerged in East Africa causing outbreaks in small livestock across different countries, with evidences of spillover to wildlife. In order to understand better PPR at the wildlife-livestock interface, we investigated patterns of peste des petits

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

6
4

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 50 publications
0
30
0
1
Order By: Relevance
“…However, based on partial genome sequencing, the virus strains detected in this study were almost identical, and therefore the variation in observed clinical signs between the four flocks from which sequences were obtained ( Table 1) was most likely due to host or environmental factors or co-infections rather than virus genotype. The circulation of multiple lineages of PPRV in Tanzania reflects multiple introductions, most likely through transboundary movements of infected small ruminants for trade or migration from neighbouring countries where PPRV is also considered to be endemic and multiple lineages have been detected-Kenya, Uganda, Rwanda, Burundi and the Democratic Republic of the Congo [66][67][68][69][70]. However, the live attenuated PPRV vaccine (Nigeria/75/1) is reported to provide protection against all the lineages [71].…”
Section: Discussionmentioning
confidence: 99%
“…However, based on partial genome sequencing, the virus strains detected in this study were almost identical, and therefore the variation in observed clinical signs between the four flocks from which sequences were obtained ( Table 1) was most likely due to host or environmental factors or co-infections rather than virus genotype. The circulation of multiple lineages of PPRV in Tanzania reflects multiple introductions, most likely through transboundary movements of infected small ruminants for trade or migration from neighbouring countries where PPRV is also considered to be endemic and multiple lineages have been detected-Kenya, Uganda, Rwanda, Burundi and the Democratic Republic of the Congo [66][67][68][69][70]. However, the live attenuated PPRV vaccine (Nigeria/75/1) is reported to provide protection against all the lineages [71].…”
Section: Discussionmentioning
confidence: 99%
“…In each province, farms were randomly selected. Fifteen animals per farm were sampled to ensure a 95% probability of detecting at least one positive animal for an assumed minimum within‐farm prevalence of 20.0% (Fernandez Aguilar et al, 2020; Mahamat et al., 2018). Systematic sampling was used to select animals on individual farms.…”
Section: Methodsmentioning
confidence: 99%
“…PPR was first described as a rinderpest (RP)-like disease of small domestic ruminants. However, in the recent-past PPRV has been reported to infect not only goats and sheep, but also camels [13], cattle [14], water buffalo [15,16], and wildlife species, including African buffalo [17,18], saiga antelope [19,20], dorcas gazelles [19,21], gemsbok [22], Nubian ibex [23], and some other wild ungulate species [19,20]. Reports of PPRV detection in Asiatic lions [24] and dogs [3,25] may reflect contamination of their food with infected ruminants, but their competence as hosts has not been established [13,[26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%